Design and Construction of an Arduino-Based Main Engine Overheating Detection Prototype - Mohamad Faris Setiyawan; Agus Prawoto; Dyah Ratnaningsih; Monika Retno Gunarti; Shofa Dai Robbi (International Journal of Science and Environment (IJSE), 2026)
Overheating in the ship's main engine, often caused by suboptimal cooling and lubrication systems, poses a high risk to performance and safety. This study aims to design and build an Arduino-based detector prototype. Using a research and development (R&D) method with an experimental approach, the population of b diesel at the Surabaya Maritime Polytechnic, a purposive sample of one Mitsubishi S6B3-MPTA unit. Instruments include Arduino Uno, thermocouple and SW200D sensors, LCD, buzzer, and Wemos D1 Mini integrated with Blynk; quantitative descriptive data analysis through Arduino IDE, comparing readings with a thermogun and connectivity tests. The results show high accuracy of temperature detection (dynamic trend 30.75-34°C), vibration (2-7 mm/s), and IoT range up to 185 m non-obstacle. In conclusion, the prototype effectively provides real-time warnings, improving preventive maintenance.